(3WHs - (3GdSeQbfOj, CHh MGeO, fLjH GdOjf, eMeO Hf Ydj Hf YeQ, (B619 (3g`s; (3CHh Ydj GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , J (B427 (3g`s
(3ChdgG (B:s
(3HSe Gddg Gfj bO LeYJ dGLdj aj gPg GdeLdI eG cGfJ MGLJj Edjg GVWQGQjI YfO eTGgOI GdeQVi heYGdLJge djchf OGFeG Hjf jOj CfXQ ajgG hCSJZfj HgG Yf GdfXQ aj cJH TJi s
(3BNQgG (B:s
(3dG JMJQb hEf WQMJ aj GdCJhf CWaCJ fGQg hjYQV def YVJg hLY TOjO hGdJgGH aj GdHOf hhQe h aj GddSGf hYOI hMPQ hcKjQ GeG jYQV GShOGO YVh Ydi Tcd eSJOjQ s
(3JHUQI GdYfhGf (B:s
(3QSGdI LGeYI aj GdWH hGdCOhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\280s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
Keywords: (3GdWHs